PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VISUAL TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH BAHASA INGGRIS - Vidya Dwi Amalia Zati; Anifah Anifah; Sani Susanti; Yasaratodo Wau (Journal Education for All : Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2020)
The purpose of this study was to determine the effect of the use of learning media on student learning outcomes in English courses. This research is a descriptive study with a quantitative approach to see how the effect of the use of visual learning media on student learning outcomes in English courses at the Department of Community Education - FIP Unimed. Based on the results of the research data analysis, it can be concluded that there is the large influence of the use of visual learning media on the learning outcomes of the Public Education students that indicated by the post-test results after being given treatment with visual learning media in English courses, then the lowest score obtained is 68 and the highest score is 93. The results of the calculation obtained an average score of 80.00, a standard deviation of 5.4, a variance score of 30.14, then a median score of 80 and a mode score of 84. From the data above, it shows that the results of the learning ability of Community Education students in the English course after being given treatment show a significant increase in Public Education students at the State University of Medan.